PTU-156 Assessing Current UK Practice for Endoscopic Surveillance in Achalasia. (17th August 2016) - Sinha, R; Wyman, A; Ellison, H; O'Shea, C; Bramble, M
Abstract : Introduction: There are no established guidelines on achalasia surveillance from the British Society of Gastroenterology(BSG)or the American Society for Gastrointestinal Endoscopy(ASGE).In the absence of guidance, conflicting evidence 1, 2 and lack of consensus amongst global experts, 3 a varied clinical practice prevails in the UK.The aim of this study was to document current clinical practice among UK endoscopists regarding achalasia surveillance. Methods: An online survey was conducted using SurveyMonkey® endorsed by BSG, AUGIS(Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland)and JAG(Joint Advisory Group on GI Endoscopy).The link was emailed to all the registered members.The first round was conducted in March2015 with a reminder later in August2015. Results: The response rate was 71% inclusive of both rounds.Overall 80%of respondents had been performing gastroscopy for over a decade and 68%declared an interest in achalasia and upper gastrointestinal cancer.Almost all(98%)had either diagnosed or performed gastroscopy in patients with achalasia and 62%performed biopsy but only if there was a macroscopic lesion at the time of the index gastroscopy.22%of the respondents performed routine random biopsy of distal oesophagus but only 1.3%used lugol's iodine to target biopsies.Despite the high levels of interest, 79%of the respondents did not undertake cancer surveillance in achalasia.Of those who did, less than a quarter(21%)proposed surveillance either after a fixed duration of diagnosis or completion of treatment; majority (80%)proposing a surveillance gastroscopy every 2–3 years whilst 18%recommended every 5 years.Most (58%)performed endoscopic inspection for a macroscopic lesion;26%performed random distal biopsies and 16% used lugol's iodine during surveillance. 93%of respondents had no anecdotal experience of malignancy arising on a background of previously diagnosed achalasia. Conclusion: The majority of specialists do not endorse cancer surveillance in achalasia based on a very low perceived risk and anecdotal experience.There is a need for establishing a national database to study the natural history, long-term management and cost-effectiveness of surveillance.It would be helpful for the BSG to recommend against surveillance, highlighting the lack of sufficient evidence and enthusiasm as judged by current clinical practice. References: 1 LeeuwenburghI, et al . Long-term esophageal cancer risk in patients with primary achalasia:a prospective study. Am J Gastroenterol 2010:2144–2149. 2 Brucher BL, et al . Achalasia and esophageal cancer: incidence, prevalence and prognosis. World J Surg 2001:745–749. 3 Ravi K, et al . Esophageal Cancer screening in Achalasia: Is there a consensus? Gastroenterology 2014;146S–682. Disclosure of Interest: None Declared